2022
DOI: 10.1021/acs.nanolett.1c04818
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Binary Visual and Fluorescence Detection of Tetanus Toxoid in Clinical Samples Based on Enzyme-Free Parallel Hybrid Chain Reaction

Abstract: Here, we report a simple aptamer-based toxoid test with both fluorescence and binary visual readouts. This test is established based on our recent finding that CdTe quantum dots could differentiate DNA templated Cu NPs from Cu2+. Through the further integration with enzyme-free triple parallel hybridization chain reaction, cation exchange reaction, and inkjet printing, we demonstrated specific detection of tetanus toxoid with a limit-of-detection (LOD) of 0.25 fg/mL using fluorescence readout. Using color- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 31 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27] The typical catalytic DNA circuit-based signal amplication strategies mediated via TSDR include the so-called catalytic hairpin DNA assembly (CHA) and hybridization chain reactions (HCR). [28][29][30][31][32][33] They usually take advantage of the metastable nucleic acid hairpins that act as assembly units, and thus their thermodynamic tendency for stable assembly even in the absence of the targets poses unfavorable challenges to the sensing performance. Further, very careful design of the assembly units and thorough optimization of the experimental conditions are usually needed for the analysis of different targets, which limits their application generality to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27] The typical catalytic DNA circuit-based signal amplication strategies mediated via TSDR include the so-called catalytic hairpin DNA assembly (CHA) and hybridization chain reactions (HCR). [28][29][30][31][32][33] They usually take advantage of the metastable nucleic acid hairpins that act as assembly units, and thus their thermodynamic tendency for stable assembly even in the absence of the targets poses unfavorable challenges to the sensing performance. Further, very careful design of the assembly units and thorough optimization of the experimental conditions are usually needed for the analysis of different targets, which limits their application generality to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, nucleic acid aptamers that are simple to synthesize, easy to store, economical, and easy to introduce functional groups have received extensive attention in sensing fields . In addition, the biggest benefit of nucleic acid aptamers as recognition probes is the ease with which multiple nucleic acid amplification strategies may be integrated to enhance the detection sensitivity of the method. Among several signal amplification techniques, enzyme-free nucleic acid- and nanomaterial-assisted methods such as nonenzyme-catalyzed hairpin assembly (CHA), hybrid chain reaction, and DNAzyme amplification technologies have been widely used by the virtue of their simple and economical design and favorable amplification effect. Especially, CHA endows with higher catalytic efficiency, lower background signals, and a simpler and more stable reaction system . In amplification technologies involving nanomaterials, materials with luminescent properties can boost analytical sensitivity while laying the foundation for the construction of analytical methods for visual reading. For instance, quantum dots (QDs), nanoclusters, N -methyl mesoporphyrin IX (NMM) small molecules, lanthanide coordination complexes, and so forth have been applied in the sensing field.…”
Section: Introductionmentioning
confidence: 99%
“…These tools integrate enzyme-free/single-enzyme (terminal deoxynucleotidyl transferase (TdT)) amplification and the selective recognition phenomenon of quantum dots (QDs) (QDs with Ag + /C− Ag + −C, Cu 2+ /copper nanoparticles (Cu NPs)). 17,20,21 In addition, the selective recognition phenomenon based on nanomaterials will enhance the homogeneous manipulation of the system, which is simple to design at a relatively acceptable cost. 22,23 Our previous studies showed the phenomenon of sterically hindered regulation of the TdT-catalyzed polymerization elongation reaction, while pyrophosphate−cerium coordination polymeric nanoparticles (PPi-Ce CPNs) can selectively recognize Cu 2+ and poly-T-templated Cu NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Nucleic acid amplification techniques can be divided into protease and nonprotease-involving methods. The protease methods utilize enzymes such as polymerases, exonucleases, or endonucleases. Enzyme-free nucleic acid amplification technologies mainly include catalyzed hairpin assembly, hybrid chain reaction, DNAzyme, etc. On the other hand, most of the nanomaterial-assisted amplifications are anchored on enzyme-like activity, many metal ions, the inertness of nanomaterials, etc. , However, the amplification of a single pure nucleic acid or nanomaterial is still limited. In addition, the development of ultrasensitive analysis tools would elevate the difficulty of sequence and experimental design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation